2020
DOI: 10.1038/s41467-020-14310-3
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell and cell-free DNA analyses for detection of residual disease in gastric cancer

Abstract: Liquid biopsies are providing new opportunities for detection of residual disease in cell-free DNA (cfDNA) after surgery but may be confounded through identification of alterations arising from clonal hematopoiesis. Here, we identify circulating tumor-derived DNA (ctDNA) alterations through ultrasensitive targeted sequencing analyses of matched cfDNA and white blood cells from the same patient. We apply this approach to analyze samples from patients in the CRITICS trial, a phase III randomized controlled study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
154
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(164 citation statements)
references
References 59 publications
9
154
0
1
Order By: Relevance
“…To analyze the association between cfDNA CNVs and HCC prognosis, genome-wide CNVs was taken into consideration rstly. As reported in previous studies, TFx could be used as a prognostic biomarker for HCC patients who received surgical resection and adjuvant therapies (25). Based on an extended sample size, similar result was also observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To analyze the association between cfDNA CNVs and HCC prognosis, genome-wide CNVs was taken into consideration rstly. As reported in previous studies, TFx could be used as a prognostic biomarker for HCC patients who received surgical resection and adjuvant therapies (25). Based on an extended sample size, similar result was also observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…A possible explanation is that the detectable CNVs were diluted by predominantly normal cfDNA as background from white blood cell (WBC) (24). Further comparison of CNV pro les between cfDNA and WBC DNA will broaden our understanding on the in uence of normal cfDNA on the detection of CNVs (25).…”
Section: Discussionmentioning
confidence: 99%
“…After a median follow-up of 42 months, all 11 patients without detectable tumor-specific mutations at the postoperative timepoint were alive and free of recurrence. On the other hand, six out of nine patients with detectable tumor-specific mutations at the postoperative timepoint developed disease recurrence and died from metastatic diseases [75]. Another recent paper in patients with operable colon cancer demonstrated a similar utility of cDNA.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 89%
“…Several recent studies have suggested that CH mutations present a challenge for proper filtering in highly sensitive NGS-based liquid biopsy assays [26][27][28] . We observed that the use of patient-matched normal WBC DNA in MSK-ACCESS eliminated 7,760 (77%) of variant calls below 10% VAF (Figure 4A-IV).…”
Section: Assessing the Filtering Of Putative Clonal Hematopoiesis (Chmentioning
confidence: 99%
“…We posited that the majority of these calls represent potential CH mutations. Recent reports 29 have suggested that fragments supporting CH variants have length distributions similar to cfDNA derived from non-cancerous cells and distinct from ctDNA 26,28,30 . Indeed, the sequence reads harboring variants with plasma VAF <10% and present in WBCs exhibited fragment lengths indistinguishable from wild-type and germline variants ( Figure 4C-IV) (bootstrapped p value = 0.99), adding confidence to the hypothesis that these were properly filtered WBC-derived somatic mutations associated with clonal hematopoiesis.…”
Section: Assessing the Filtering Of Putative Clonal Hematopoiesis (Chmentioning
confidence: 99%